Paid holiday entitlements, weekly working hours and earnings in the UK - Bryan, Mark L. (Colchester, 2006)
"Paid holiday entitlements are similar on average in the UK to other western European countries, but there is much more variation across jobs in the UK. This paper examines the determinants of paid holiday entitlements for full-time UK workers and the relationship of entitlements to earnings. Holiday entitlements are strongly related to educational qualifications, occupation, job tenure and other employer characteristics. However, these factors cannot explain most of the variation in entitlements, implying there is a wide range of remuneration policies across otherwise similar employers or that some workers manage to obtain higher levels of holiday entitlement than other comparable workers. Longer holiday entitlements are associated with higher earnings, even after controlling for human capital and job characteristics, so that earnings differentials are additional not compensating. By contrast, shorter weekly work hours are associated with lower earnings. Unmeasured skill accumulation or improvements in job match quality appear to be associated with longer holiday entitlements (and higher earnings) but to have little relation to weekly working hours."